Prevalence of Metabolic Syndrom in Three Urban Communities of Dhaka City (Ibrahim Medical College Journal, 2009)
Bangladeshis are prone to develop type 2 diabetes mellitus (T2DM), hypertension (sHTN and dHTN) and atherosclerotic heart diseases, observed more predominantly in the urban population. Though metabolic syndrome (MetS) is a related disorder, there are few studies in this regard. The prevalence of obesity, T2DM and MetS in three urban communities of Bangladesh were addressed in this study. Nine hundred non-slum urban households in three Dhaka City Wards were randomly selected. One member (age ≥ 25y) from each household was invited for investigation with an overnight fast. Socio-demographic information as well as height, weight, waist-girth, hip-girth and blood pressure were measured. Fasting plasma glucose (FPG), total cholesterol (chol), triglycerides (TG) and high-density lipoproteins-c (HDL) were estimated. A total of 705 (m / f = 239 / 466) subjects volunteered for the study. The mean value with 95% confidence interval (CI) of age was 42.4 (40.9 - 43.1) years for men and 37.8 (36.8 - 38.7) for women. The mean (CI) body mass index (BMI) was 21.0 (20.6 - 21.5) and 22.6 (22.2 - 22.9) and waist hip ratio (WHR) was 0.84 (0.83 - 0.84) and 0.82 (0.81 - 0.83), respectively for men and women. The mean (CI) FPG (fasting plasma glucose) was 5.5 (5.2 - 5.7) for men and 5.2 (5.0 - 5.4) for women. The prevalence of obesity (BMI ≥ 25.0) was 21%, T2DM (FPG ≥ 6.1 mmol/l) was 22.2%, triglyceridemia (TG ≥ 150mg/dl) was 45.1% and low HDL-c (HDL